Class in Czechia: The Legacy of Stratification Research. (August 2015) - Drahokoupil, Jan
This essay discusses the use of class in Czech sociology. Czech social stratification research has used the concept of class as part of its standard vocabulary. The approach to class was distinctively shaped by postcommunist legacies. As an analytical concept, socio-economic status was preferred over class, particularly in the 1990s. The middle class played a prominent role as a subject of research and also a rallying cry. An important legacy that shaped the approach was the intellectual formation of Czech sociologists through the critique of the social stratification system in state socialism. This specific form of anticommunism shaped the type of questions typically asked in the stratification research and its subject matter. Moreover, the anticommunist legacy shaped interpretations of the broader implications of the stratification mechanisms and class effects, giving rise to an overly functionalist approach to the class system.